2007
DOI: 10.1111/j.1365-2923.2007.02832.x
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news: consultants' experience, previous education and views on educational format and timing

Abstract: Consultants in clinical specialties break bad news frequently. Although many have not received formal training, the majority believe it is useful and are increasingly willing to undertake experiential approaches. This augurs well for future training programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 28 publications
0
34
0
5
Order By: Relevance
“…2,10,14 One prior study found no significant difference. 15 Responses to the open-ended questions showed that the curriculum intervention did result in an improvement in empowering message strategies for breaking bad news, similar to a finding by another group.…”
Section: Discussionmentioning
confidence: 97%
“…2,10,14 One prior study found no significant difference. 15 Responses to the open-ended questions showed that the curriculum intervention did result in an improvement in empowering message strategies for breaking bad news, similar to a finding by another group.…”
Section: Discussionmentioning
confidence: 97%
“…Effective and appropriate training that provides opportunity for residents to increase awareness of their own attitudes and reactions to DDN may assist them to feel more skilled and confident. 11,36,37 Trainees should be encouraged to be present when bad news is provided by senior clinicians. Students and residents will quickly learn that there are different techniques and personal styles and that they can creatively adapt these styles into their own work with patients-which will, in turn, better enable them to identify individual patients' specific needs and concerns.…”
Section: What Is Happening In Practice?mentioning
confidence: 99%
“…A broad range of professional disciplines are responsible for informing families about their child's disability (or raising concerns) depending on the diagnosis type, timing and the service context 5. The diagnosis can be given by professionals with varied levels of experience and confidence, in various service settings, and by medical, nursing and allied health professions 4.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that postgraduate healthcare professionals have received low levels of formal training in breaking difficult news, showing between half and three-quarters of respondents without any previous instruction 5 8. Other studies found that those who had recently completed their education had largely received training in breaking difficult news 13.…”
Section: Introductionmentioning
confidence: 99%